World electric vehicle journal - World Electric Vehicle Association ([Avere aisbl], 2007)
"The primary scientific journal serving the interests of the international electric vehicle community."
Keywords: Electric vehicles : Periodicals; Hybrid electric vehicles : Periodicals; Fuel cell vehicles : Periodicals; Electric vehicles; Fuel cell vehicles; Hybrid electric vehicles; Automotive Engineering